2017
DOI: 10.15252/emmm.201607445
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stroma reorganization drives blood vessel dysmorphia during glioma growth

Abstract: Glioma growth and progression are characterized by abundant development of blood vessels that are highly aberrant and poorly functional, with detrimental consequences for drug delivery efficacy. The mechanisms driving this vessel dysmorphia during tumor progression are poorly understood. Using longitudinal intravital imaging in a mouse glioma model, we identify that dynamic sprouting and functional morphogenesis of a highly branched vessel network characterize the initial tumor growth, dramatically changing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 63 publications
5
73
0
Order By: Relevance
“…Subsequently, the Ang1/Ang2‐Tie2 signals regulate endothelial cell survival, vascular assembly by incorporating pericytes, and stabilization and maturation of new vessels . This is the process that occurs under most pathophysiological conditions but dysregulation of the steps may be involved in the formation of the aberrant GBM microvasculature, which is composed of disorganized endothelial cells and pericytes . Although no in vitro assays were available to explore the molecular basis of this complex neovascularization, we developed the novel endothelial cells–pericytes coculture assay and succeeded in forming multilayered irregularly shaped tube‐like structures of HUVEC only under stimulation with a very high concentration (500 ng/ml) of VEGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the Ang1/Ang2‐Tie2 signals regulate endothelial cell survival, vascular assembly by incorporating pericytes, and stabilization and maturation of new vessels . This is the process that occurs under most pathophysiological conditions but dysregulation of the steps may be involved in the formation of the aberrant GBM microvasculature, which is composed of disorganized endothelial cells and pericytes . Although no in vitro assays were available to explore the molecular basis of this complex neovascularization, we developed the novel endothelial cells–pericytes coculture assay and succeeded in forming multilayered irregularly shaped tube‐like structures of HUVEC only under stimulation with a very high concentration (500 ng/ml) of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…9 This is the process that occurs under most pathophysiological conditions but dysregulation of the steps may be involved in the formation of the aberrant GBM microvasculature, which is composed of disorganized endothelial cells and pericytes. 41 Although no in vitro assays were available to explore the molecular basis of this complex neovascularization, we developed the novel endothelial cells-pericytes coculture assay and succeeded in forming multilayered irregularly shaped tube-like structures of HUVEC only under stimulation with a very high concentration (500 ng/ml) of VEGF. The results from our double-immunostaining and inhibition studies provide direct evidence that Fbln7 is indispensable to the formation of VEGFinduced aberrant tube-like structures of endothelial cells through interaction with pericytes.…”
Section: Discussionmentioning
confidence: 99%
“…Some specific morphological characteristics were extracted from MPM images. First, the uneven and abnormal structure of blood vessels in gliomas is the key features . In the normal brain tissues, the capillary or tube‐shaped blood vessels were usually thin, small and regular.…”
Section: Discussionmentioning
confidence: 99%
“…Intravital microscopy has emerged as an indispensable tool in studying the complex tumor microenvironment in situ , with the possibility of following in real time the dynamic interactions between cancer cells, immune cells, vasculature, and the extracellular matrix, and of following tumor growth and invasion longitudinally via imaging windows. In the study by Mathivet et al (; see Fig for a graphical summary of the findings), gliomas arising from intracranially injected spheroids were first imaged by two‐photon microscopy through a cranial window at 2 weeks postimplantation. The authors found that at this stage, angiogenesis was proceeding in an orderly fashion, with tip cell‐guided sprouting and without the characteristics of aberrant angiogenesis normally observed in tumors.…”
Section: Macrophage Depletion Treatment By Targeting Csf‐1 In Combinmentioning
confidence: 99%
“…Tumor angiogenesis is known to be supported by host leukocytes recruited to the tumor microenvironment, but the mechanisms leading to dysfunctional vascular network formation are incompletely understood. In this issue of EMBO Molecular Medicine , Mathivet et al () present an elegant study, where longitudinal intravital imaging gives new insight on how recruitment and polarization of tumor‐associated macrophages regulate aberrant angiogenesis in experimental gliomas. They show that macrophage targeting results in vessel normalization and improved chemotherapy response, suggesting that the combination of these therapeutic modalities could improve the outcome of glioma treatment in the clinic.…”
mentioning
confidence: 99%